Intracellularly Localized PIN-FORMED8 Promotes Lateral Root Emergence in Arabidopsis - Lee, Hyodong; Ganguly, Anindya; Lee, Richard Dongwook; Park, Minho; Cho, Hyung-Taeg (Frontiers in Plant Science, 2020)
PIN-FORMED (PIN) auxin efflux carriers with a long central hydrophilic loop (long PINs) have been implicated in organogenesis. However, the role of short hydrophilic loop PINs (short PINs) in organogenesis is largely unknown. In this study, we investigated the role of a short PIN, PIN8, in lateral root (LR) development in Arabidopsis thaliana. The loss-of-function mutation in PIN8 significantly decreased LR density, mostly by affecting the emergence stage. PIN8 showed a sporadic expression pattern along the root vascular cells in the phloem, where the PIN8 protein predominantly localized to intracellular compartments. During LR primordium development, PIN8 was expressed at the late stage. Plasma membrane (PM)-localized long PINs suppressed LR formation when expressed in the PIN8 domain. Conversely, an auxin influx carrier, AUX1, restored the wild-type (WT) LR density when expressed in the PIN8 domain of the pin8 mutant root. Moreover, LR emergence was considerably inhibited when AXR2-1, the dominant negative form of Aux/IAA7, compromised auxin signaling in the PIN8 domain. Consistent with these observations, the expression of many genes implicated in late LR development was suppressed in the pin8 mutant compared with the WT. Our results suggest that the intracellularly localized PIN8 affects LR development most likely by modulating intracellular auxin translocation. Thus, the function of PIN8 is distinctive from that of PM-localized long PINs, where they generate local auxin gradients for organogenesis by conducting cell-to-cell auxin reflux.